Segmental Suture Gonioscopy-Assisted Transluminal Trabeculotomy: Comparison of Superior Versus Inferior Hemisphere Outcomes. Issue 5 (28th May 2023) - Waldner, Derek M.; Chaban, Yuri; Penny, Michael D.; Al-Ani, Abdullah; Belkin, Avner; Ahmed, Iqbal Ike K.; Schlenker, Matthew B.; Gooi, Patrick
Abstract : Précis: Analysis of efficacy, safety, and risk factors for failure of superior versus inferior 180-degree segmental gonioscopy-assisted transluminal trabeculectomy showed no significant difference between approaches, with novel risk factors for failure identified. Purpose: Compare the efficacy, safety, and risk factors for failure of superior versus inferior 180-degree segmental suture gonioscopy-assisted transluminal trabeculotomy (GATT). Design: Multicenter, retrospective interventional cohort study of 297 eyes of 243 glaucomatous patients, which underwent superior or inferior 180-degree suture hemi-GATT surgery combined with phacoemulsification at one of 3 Canadian ophthalmological surgical centres in Calgary, Alberta or Toronto, Ontario Main Outcome Measures: The primary outcome measure was the hazard ratio (HR) of failure for the "primary success" criteria. "Primary success" was defined as an intraocular pressure (IOP) <18 mm Hg and either 1) IOP reduced by ≥20% from baseline on the same number of IOP-lowering medications or 2) IOP ≤ baseline on fewer medications. Secondary outcome measures included HRs of failure for alternative criteria ("complete success", "qualified success" and "20% IOP reduction"), cross-sectional analysis, and Cox proportional hazard analysis for risk factors associated with increased failure for the complete cohort. Results: Baseline characteristics were similar between groups. The crude and adjusted HR of failure for the "primary success" criteria for superior surgeries relative to inferior surgeries were 1.27 (95% CI = 0.86–1.88) and 1.50 (95% CI = 0.91–2.46), with no statistically significant difference between approaches. Of the secondary criteria, there was statistical significance in favor of inferior surgeries only for crude analysis of the "20% reduction" criteria (1.40/1.27 (95% CI = 1.01–1.92). Increased risk of failure by the "primary success" measure for either intervention was seen with primary open angle glaucoma, advanced disease, and age below 70 years. There were no significant differences in the frequency of postoperative complications between cohorts, which were present in 72 superior (44.4%) and 67 inferior (49.6%; P value = 0.41) eyes; mostly early postoperative hyphema, iritis, and corneal edema. Conclusions: This retrospective study showed no difference in inferior versus superior 180 degrees of hemi-GATT/phacoemulsification cataract surgeries through the majority of analyses. Nonmodifiable factors including glaucoma type, advanced disease, and younger age were associated with a significantly higher risk of failure in this cohort. Further study is warranted.